Perspectives on the integration of students with disabilities in physical education: An umbrella review of reviews published between 2010 and 2020 - Andreas Fröberg (European Federation of Adapted Physical Activity, 2021)
Research regarding the integration of students with disabilities in physical education has progressively increased during the last three decades, as has the number of published reviews. The objective of this umbrella review was to synthesise findings from reviews published between 2010 and 2020 to obtain a comprehensive picture of the current literature regarding the integration of students with disabilities in physical education. Search strings were developed and the four electronic databases Educational Research Complete, ERIC, Scopus, and SportDiscus were searched to identify reviews published between January 2010 and January 2020. After removing duplicates, 117 individual documents were screened and reviewed for eligibility, and eight reviews published between 2012 and 2019 were included. These reviews included quantitative, qualitative, and mix methods research. From the reviews, to some degree, SWDs, SWODs and PETs have mixed experiences from and ambiguous attitudes towards the integration of SWDs in PE.